2000
DOI: 10.1212/wnl.54.2.302
|View full text |Cite
|
Sign up to set email alerts
|

Chinook winds and migraine headache

Abstract: Both prechinook and high-wind chinook days increase the probability of migraine onset in a subset of migraineurs. Because few subjects were found to be sensitive to both weather types, the mechanisms for these weather effects may be independent. This is supported by the presence of an age interaction for high-wind chinook days but not for prechinooks day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
77
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 9 publications
6
77
1
1
Order By: Relevance
“…The mechanisms of the strong wind influence on human health and behaviour are not known. Some authors believe that adverse consequences of the strong wind on human health are due to negative effects of environmental concomitants such as ambient temperature, barometric pressure, positive ion concentrations, and so on [21]. Our analysis yield, the apparent relation of the high DHAI effects with the WV including the evident correspondence of the high DHAI with the high WV, which supports the suggestion that the high APFs are a general physical agent provoking biological response to these two atmospheric factors.…”
Section: Discussionsupporting
confidence: 85%
“…The mechanisms of the strong wind influence on human health and behaviour are not known. Some authors believe that adverse consequences of the strong wind on human health are due to negative effects of environmental concomitants such as ambient temperature, barometric pressure, positive ion concentrations, and so on [21]. Our analysis yield, the apparent relation of the high DHAI effects with the WV including the evident correspondence of the high DHAI with the high WV, which supports the suggestion that the high APFs are a general physical agent provoking biological response to these two atmospheric factors.…”
Section: Discussionsupporting
confidence: 85%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Premonitory features include changes in mood or behavior that precede the onset of an attack. Trigger factors, measurable precipitants associated with an increased probability of an attack, can include stressful events, hormonal changes, weather changes, and certain foods, although some studies demonstrate reduced odds for migraine attacks in relation to certain variables.…”
Section: Objectivementioning
confidence: 99%
“…Trigger factors, measurable precipitants associated with an increased probability of an attack, can include stressful events, hormonal changes, weather changes, and certain foods, although some studies demonstrate reduced odds for migraine attacks in relation to certain variables. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] In patient surveys, perceived stress was associated with migraine onset in up to 80% of respondents. [13][14][15][16] Diary studies have shown that "daily hassles" significantly increase in the 2-to 3-day period before a migraine day.…”
mentioning
confidence: 99%
“…Others have shown at least some associations between certain weather conditions and migraine occurrence (10)(11)(12)(13)(14)(15), but no consistent picture of which weather-related factors are important migraine triggers has emerged.…”
mentioning
confidence: 99%